2005
DOI: 10.1080/09670260500342696
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural study of the brown algaPetroderma maculiforme(Phaeophyceae) in the free-living state and in lichen symbiosis with the intertidal marine fungusVerrucaria tavaresiae(Ascomycotina)

Abstract: A comparative TEM study was carried out on the phaeophyte Petroderma maculiforme, collected from San Francisco Bay both as free-living thalli and as phycobiont of the lichen fungus Verrucaria tavaresiae. The free-living alga usually had thicker cell walls and substantially greater reserves in storage bodies than the lichenized form. Cell division patterns were altered in symbiosis, and formation of zoosporangia was not observed on the lichenized filaments. Both free-living and lichenized Petroderma showed an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Polyphenols are known to be involved in the interactions between vascular plants and symbiotic fungi; in particular, mycorrhizal infection leads to changes in polyphenolic profiles [ 55 , 56 ]. Sanders et al [ 57 ] showed that the brown alga Petroderma maculiforme , occurring in both free-living and lichenized state, continued producing high abundance of physodes under the nutritional burden of supporting a fungal symbiont. Together with our results, this data suggests that certain phlorotannins (presumably, dhE/C series) may contribute to alga–fungus interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Polyphenols are known to be involved in the interactions between vascular plants and symbiotic fungi; in particular, mycorrhizal infection leads to changes in polyphenolic profiles [ 55 , 56 ]. Sanders et al [ 57 ] showed that the brown alga Petroderma maculiforme , occurring in both free-living and lichenized state, continued producing high abundance of physodes under the nutritional burden of supporting a fungal symbiont. Together with our results, this data suggests that certain phlorotannins (presumably, dhE/C series) may contribute to alga–fungus interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although photobionts belong to very diverse groups of organisms, the only major groups of algae represented those that include multicellular species i.e. not only the green algae (Chlorophycae) but now also the red algae (Phaeospora lemaneae and a species of red alga probably Lemanea sp., Rhodophycae; Hawksworth, 1987Hawksworth, , 1988Hill, 1992a) and the brown algae (Petroderma maculiforme, Phaeophycae; Sanders et al, 2005). All these groups capable of multicellular organisation have physiological features in common (e.g.…”
Section: Understanding the Main Basis Of The Symbiosismentioning
confidence: 99%
“…2D) but not readily visible with light microscopy. The pyrenoids are traversed by branching tubules arising from invagination of the plastidial boundary membranes (rather than thylakoids, as in Trebouxia and Heveochlorella); the position of the pyrenoid may be laminar, protruding to exserted, or enfolded by chloroplast lobes (Sanders et al 2005). The alga was first brought to the attention of lichenologists by a footnote in a phycology dissertation (Wynne 1969) that reported it in symbiosis with a Verrucaria species on intertidal rocks in northern California.…”
Section: Stramenopila (Heterokontae)mentioning
confidence: 99%